2007
DOI: 10.1016/j.crvi.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Recherche prospective sur le rôle « source » des haies en production fruitière intégrée. Le cas des perce-oreilles : Forficula auricularia L. et Forficula pubescens Gené

Abstract: L'influence de l'occupation du sol, en bordure des parcelles cultivées, sur les peuplements en arthropodes et la régulation des effectifs de ravageurs fait des haies un objet d'études majeur. Existe-t-il des échanges de population entre haie et vergers qui font de la haie une source ou un puit d'espèces vis-à-vis de la parcelle cultivée ? Dans le cadre de recherches de stratégies innovantes dans la lutte contre les bioagresseurs en arboriculture, le rôle « source » des haies est étudié à partir du suivi des dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In our opinion, this difference is easily explained by the different sampling time. The work conducted by Santos et al (2007) was performed during the summer. In that season, the olive grove ground is without cover and has very low humidity that favors the disappearance of Collembola and the dominance of other organisms well adapted to such conditions, such as ants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, this difference is easily explained by the different sampling time. The work conducted by Santos et al (2007) was performed during the summer. In that season, the olive grove ground is without cover and has very low humidity that favors the disappearance of Collembola and the dominance of other organisms well adapted to such conditions, such as ants.…”
Section: Discussionmentioning
confidence: 99%
“…Forficula auricularia are omnivores and feed on mosses, lichens, plants, and small living or dead arthropods (Debras et al 2007). Chilopoda are almost exclusively predatory, feeding on small live arthropods and other invertebrates (Edgecombe and Giribet 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Debras et al (2007) observed that F. pubescens concentrated predation on younger pear psylla instars, whereas F. auricularia showed a preference for older ones.…”
mentioning
confidence: 84%
“…Another earwig species, Forficula pubescens Gené, has been reported to be phytophagous or omnivorous (Albouy & Caussanel, 1990); however, it has also been observed to prey on pear psyllids (Debras et al, 2007) and RAA (Dib et al, 2010). Few studies have been devoted to the phenology of F. pubescens (Herter, 1964;Romeu-Dalmau et al, 2011).…”
Section: Phenologymentioning
confidence: 99%
See 1 more Smart Citation